Seroepidemiology of peste des petits ruminants virus in small ruminants in selected districts in Northwest Ethiopia - Abesha, H.; Teshome, Y.; Alemu, Y.F.; Dejene, H.; Tarekegn, Z.S.; Assefa, Ayalew (Wiley, 2023)
Background Peste des petits ruminants (PPR) is one of the most severe diseases of small ruminants, causing the loss of millions of dollars annually. A cross-sectional study was conducted to determine the seroepidemiology of peste des petits ruminants virus (PPRV) in unvaccinated sheep and goats in selected districts in Northwest Ethiopia.